Cancer genetic alterations and risk of venous thromboembolism. Issue 213 (May 2022) - Mantha, Simon; Rak, Janusz
Abstract: Cancer has long been known to incur an increased risk of venous thromboembolism (VTE). Multiple risk factors for cancer-associated thrombosis (CAT) have been identified, and several pathophysiological mechanisms elucidated. However, until recently there was scant data available about the influence of cancer-specific somatic genetic alterations on the risk of venous thromboembolism. In the last few years, several gene loci were found to modulate the risk of CAT, usually causing an increase in risk but sometimes found to have a protective effect. Notably, cancer-specific somatic genetic alterations in KRAS, IDH1, ALK and ROS1 have been found to alter the risk of CAT by independent groups. Work in this field is limited by the high-dimensionality and often sparse nature of genomic datasets. Also, early data suggest that for certain genes the effect on VTE risk can be tumor type-specific, which suggests that predictive models must factor such interactions in order to optimally leverage genetic information. Notably, individual gene effects appear to be often small and no one gene explains most of the variability of CAT risk. Ultimately, improved knowledge of the genetic determinants of CAT will help ameliorate risk stratification for this complication and hopefully provide mechanistic insights. Better risk stratification could lead to enhanced pharmacological VTE prophylaxis, while advancements in the understanding of the biology of CAT could conceivably lead to non-anticoagulant targeted therapies for thrombosis. Highlights: Multiple genes modulate the risk of cancer-associated thrombosis Individual gene effects on cancer-associated thrombosis risk are often small and sometimes tumor type-specific Current evidence suggests that alterations in KRAS, IDH1, ALK and ROS1 influence the risk of cancer-associated thrombosis